2019
DOI: 10.25105/ber.v18i2.5334
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transformational Leadership Style, Work Motivation, and Work Environment on Employee Performance That in Mediation by Job Satisfaction Variables in Pt. Gynura Consulindo

Abstract: <p><strong><em>The objective of this research was </em></strong><em>to determine the factors that influence job satisfaction and its consequences toward employee performance at PT. Gynura Consulindo. Independent variables in this research are transformational leadership style, work motivation and work environment. The intervening variable in this research is job satisfaction and the dependent variable is employee performance.</em></p><p><strong><em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 6 publications
4
19
0
14
Order By: Relevance
“…This finding indicates that the work environment variable indirectly influences the employee performance variable and supports the third hypothesis. This finding aligns with previous studies, which found a significant positive relationship between work environment variables and employee performance variables (Priarso et al, 2019;Riyanto et al, 2017).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This finding indicates that the work environment variable indirectly influences the employee performance variable and supports the third hypothesis. This finding aligns with previous studies, which found a significant positive relationship between work environment variables and employee performance variables (Priarso et al, 2019;Riyanto et al, 2017).…”
Section: Resultssupporting
confidence: 93%
“…According to Dunggio and Rachman (2017), in achieving employee performance, companies must adapt to the condition and work environment, which is suitable and comfortable. Previous empirical findings prove a significant effect of the work environment on employee performance (Priarso et al, 2019;Riyanto et al, 2017). Therefore, based on the theory and findings of previous studies, the third hypothesis proposed in this study is: H3: The work environment affects the performance The three hypotheses proposed in this study are summarized in the following research model (Figure 2).…”
Section: Work Environmentmentioning
confidence: 95%
“…Hight debt is not accompanied by an increase in income/profits will make the weak firm performance. (Mariam & Ramli, 2019;Priarso, Diatmono & Mariam, 2018;Ramli, 2018b;Puteri & Ramli, 2018;Ramli & Maniagasi, 2018;Ramli, 2019b). This is because the Corporation must bear the interest expense and principal return on the debt, if operating profit cannot cover the interest expense, the Corporation will suffer losses (Ramli, 2017a;Chandra, Takaya & Ramli, 2019;Ramli 2017b), and the Corporation will begin to experience liquidity problems, Financial Distress and the potential for bankruptcy.…”
Section: Score) Significantlymentioning
confidence: 99%
“…Jones and Brazzel (2006). The stimulus that occurs from the environment due to the mutual relationship between a person and the environment that results in the form of a person's actual actions or from words (Du Burin, 2007;Priarso, Diatmono & Mariam, 2018).…”
Section: Business and Entrepreneurial Reviewmentioning
confidence: 99%